KELIMPAHAN CHLOROPHYTA PADA MEDIA BUDIDAYA IKAN NILA YANG DIBERI PAKAN FERMENTASI DENGAN PENAMBAHAN TEPUNG KULIT UBI KAYU DAN PROBIOTIK - Heni Andriyani; Endang Widyastuti; Dwi Sunu Widyartini (Scripta Biologica, 2014)
Chlorophyta is autotroph organisms which has an important role in fresh waters as one of the largest algae division. This study aimed to determine the abundance and similarity structure of Chlorophyta in Tilapia culture media which was given fermented feed with the addition of cassava peel flour and MEP+ probiotic. This study used four treatments with four replications: (A) fermented feed without addition of cassava peel flour or 0% and MEP+ probiotic administration in media, (B) 25%, (C) 50% and (D) 75%. Sampling was carried out 6 times at intervals of 2 weeks. The main parameters were the number of Chlorophyta species and individuals,while supporting parameters were physical (temperature and TDS) and chemical (DO, BOD, pH, NO3, NO2 and total of PO4). The abundance of Chlorophyta data were analyzed descriptively and its similarity structure were analyzed using Cluster analysis. Then, continued with SIMPER analysis to determine the contribution of species to abundance similarity with PRIMER-E v.5 software. Analysis results showed that the abundance of Chlorophyta consists of 33 species with the average number of 10.412 individuals/liter. Cluster analysis results based on Bray-Curtis similarity index had a quite high similarity and it ranged between 57.79% -68.84%. SIMPER analysis results showed that the species which given highest contribution were Kircheneriella lunaris (31,03%), Selenastrum sp. (21,69%), and Gonatozygon monotaenium (12,96%).